2020
DOI: 10.3389/fbioe.2020.00168
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Artery Stenoses Contribute to the Development of Diffuse Plaques in the Basilar Artery

Abstract: Vertebral artery (VA) stenosis is relevant to a high early risk of recurrent stroke and basilar artery (BA) is the most common intracranial site of atherosclerotic lesions. It is important to show predictive risk factors for transient ischemic attack (TIA) or posterior infarctions. The aim of the study is to investigate morphometry and hemodynamics in intracranial vertebral and basilar arteries of health and diseased patients to enhance the risk assessment. Based on the geometrical model reconstructed from CTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…It should be noted that plaque formation is not only dependent on mechanical factors but also chemical factors, 44 blood composition and lipid content, 77 hematocrit and viscosity 78 . Each of the these parameters can be important, but according to the hemodynamic outcomes of the current study (as presented in Table 4), the most critical area is region VI where the probability of plaque formation and growth is almost twice of any other marked region (full susceptibility score) which is in favor of axial growth of the primary lesion The suggested axially extended configurations of the plaques is in complete agreement with previous patient‐specific observations 79 . Then, regions III in the PF and V in the PS obtained high‐vulnerability scores.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It should be noted that plaque formation is not only dependent on mechanical factors but also chemical factors, 44 blood composition and lipid content, 77 hematocrit and viscosity 78 . Each of the these parameters can be important, but according to the hemodynamic outcomes of the current study (as presented in Table 4), the most critical area is region VI where the probability of plaque formation and growth is almost twice of any other marked region (full susceptibility score) which is in favor of axial growth of the primary lesion The suggested axially extended configurations of the plaques is in complete agreement with previous patient‐specific observations 79 . Then, regions III in the PF and V in the PS obtained high‐vulnerability scores.…”
Section: Discussionsupporting
confidence: 89%
“…78 Each of the these parameters can be important, but according to the hemodynamic outcomes of the current study (as presented in Table 4), the most critical area is region VI where the probability of plaque formation and growth is almost twice of any other marked region (full susceptibility score) which is in favor of axial growth of the primary lesion The suggested axially extended configurations of the plaques is in complete agreement with previous patient-specific observations. 79 Then, regions III in the PF and V in the PS obtained high-vulnerability scores. Any degeneration in region V indicates more constricted lumen, for example, progression from S50 to S65.…”
Section: Discussionmentioning
confidence: 99%
“…Syncope is the clinical manifestation in the posterior cerebral artery occlusion or temporary sludge flow in the vertebral artery (VA). VA stenosis is the primary risk factor for recurrent stroke [ 1 ]. All the vertebral arteries had a tortuous course and were covered with rich venous plexuses [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study observed that patients with vertebral artery stenosis had significantly high SAR-TAWSSG and a high incidence of transient ischemic attacks (TIAs) or posterior circulation infarction. Further, high SAR-TAWSSG may induce TIA or posterior circulation infarction ( 25 ). In our study, we found that higher SAR-TAWSSG both at the bifurcation and basilar artery zone of patients with BAF compared to that of those patients with normal vertebrobasilar arteries.…”
Section: Discussionmentioning
confidence: 99%